2021
DOI: 10.7759/cureus.19512
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Absidia corymbifera in a Lupus Nephritis Patient

Abstract: A 28-year-old farmer with class IV lupus nephritis presented with a two-week history of a right shin lesion. The lesion was purple in color, fungating, and indurated with a focus of deep ulceration at the inferior pole and punctate, bleeding from its surface. Three months earlier, he was started on induction immunosuppression for a relapse of his lupus nephritis. Since the diagnosis of lupus nephritis, nine years previously, he had had six flares of his disease and had been treated at different time points wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In our fungal isolates, we found pathogens of plant diseases from genera such as Pestalotiopsis [ 58 , 59 ], Volutella [ 60 , 61 ], Didymella [ 62 ], Xylaria [ 63 ], and Crinipellis [ 64 ]; the genus Coriolopsis which is associated with trees and one of the lignicolous fungi [ 65 ]; and Paraphaeosphaeria [ 66 ], Peroneutypa [ 67 ], and Phaeophlebiopsis [ 68 ], which are genera associated with the epiphytic fungi of plants. The fungi of the genus Absidia are usually isolated from soil, constituting the pathogens of many human diseases [ 69 , 70 , 71 , 72 ]. Gongronella is capable of hydrolyzing polymeric chitosan to produce oligomeric chitosan [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our fungal isolates, we found pathogens of plant diseases from genera such as Pestalotiopsis [ 58 , 59 ], Volutella [ 60 , 61 ], Didymella [ 62 ], Xylaria [ 63 ], and Crinipellis [ 64 ]; the genus Coriolopsis which is associated with trees and one of the lignicolous fungi [ 65 ]; and Paraphaeosphaeria [ 66 ], Peroneutypa [ 67 ], and Phaeophlebiopsis [ 68 ], which are genera associated with the epiphytic fungi of plants. The fungi of the genus Absidia are usually isolated from soil, constituting the pathogens of many human diseases [ 69 , 70 , 71 , 72 ]. Gongronella is capable of hydrolyzing polymeric chitosan to produce oligomeric chitosan [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that, at least in the case of voriconazole, this effect could be caused by CYP2B6 inhibition [ 104 ]. In this regard, isavuconazole acts as an inducer of this isoenzyme, so it can a priori reduce cyclophosphamide concentrations with loss of efficacy [ 102 ], although some of the published data do not seem to confirm this [ 105 ].…”
Section: Drugs Used In Hematology-oncologymentioning
confidence: 99%